2013
DOI: 10.1002/jhm.2086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of venous thromboembolism prophylaxis in patients with chronic liver disease

Abstract: BACKGROUND The incidence of venous thromboembolism (VTE) in chronic liver disease (CLD) patients has been reported to be 0.5% to 6.3%. Studies report the use of thromboprophylaxis in CLD patients as suboptimal, with at least 75% of patients receiving no prophylaxis. OBJECTIVE To describe the use of VTE prophylaxis in CLD patients. DESIGN A retrospective review. SETTING Tertiary‐care academic medical center. PATIENTS Inpatient admissions from August 2009 through July 2011 with CLD diagnosis. INTERVENTION None. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 18 publications
(64 reference statements)
2
28
0
Order By: Relevance
“…Dabbagh et al also confirmed that an elevated INR did not protect against the development of VTE during hospitalization [28]. Smith et al showed that the risk of in-hospital VTE was similar between patients with INR <2.0 and INR ≥2.0 [29]. Indeed, our team observed a positive relationship between INR and risk of VTE [30].…”
Section: Risk Factors For Vte In Liver Cirrhosissupporting
confidence: 64%
“…Dabbagh et al also confirmed that an elevated INR did not protect against the development of VTE during hospitalization [28]. Smith et al showed that the risk of in-hospital VTE was similar between patients with INR <2.0 and INR ≥2.0 [29]. Indeed, our team observed a positive relationship between INR and risk of VTE [30].…”
Section: Risk Factors For Vte In Liver Cirrhosissupporting
confidence: 64%
“…Despite this, several recent studies of anticoagulation in those with advanced fibrosis or cirrhosis appear to demonstrate acceptable safety profiles. Studies of VTE prophylaxis in cirrhotics patients have demonstrated no significantly increased risk of bleeding with anticoagulation (Intagliata et al, 2014;Smith et al, 2013, Barclay et al, 2013. Reichert and colleagues did demonstrate that if the INR was greater than 1.5, then the risk of bleeding was increased, but this was only for bleeding classified as of minor severity (Reichert et al, 2014) and stratification by type of anticoagulation has demonstrated that unfractionated heparin results in a higher bleeding risk than low molecular weight heparin in cirrhotic patients (Intagliata et al, 2014).…”
Section: How Safe Is Anticoagulation Therapy To Use In Those With Chrmentioning
confidence: 99%
“…Studies investigating the relationship between the use of prophylactic anticoagulation in patients with cirrhosis and the risk of VTE have given contradictory results, perhaps reflecting the fact that these are predominantly retrospective studies with differences in coding and/ or means of defining cases of chronic liver disease, More specifically, some studies have failed to demonstrate a significant difference in the incidence of venous thromboembolic events in people with chronic liver disease given prophylactic anticoagulation compared to those who were not (Dabbagh et al, 2010), or observed no significant difference between incidence of VTE in those treated with pharmacological, mechanical or no prophylaxis (Smith et al, 2013). In contrast, other studies have shown a decreased incidence of VTE in patients with chronic liver disease given pharmacological prophylaxis (Barclay et al, 2013).…”
mentioning
confidence: 99%
“…7 However, in clinical settings, patients with liver cirrhosis are still broadly considered as having a bleeding diathesis, and increasing PT/INR and aPTT continue to be widely used as bleeding risk assessment parameters in patients with liver cirrhosis. 14,15 Moreover, several bleeding risk assessment scores include an abnormal liver function, which is differently defined by the various scores: increasing PT/INR, 16 biochemical evidence of liver dysfunction (HAS-BLED score; liver cirrhosis or increased bilirubin and transaminases) 17 or not specified (HEMORR2AGES score). 18 This contradicts the accumulating evidence of a procoagulant profile in patients with liver cirrhosis, which worsens in parallel to cirrhosis severity.…”
Section: Introductionmentioning
confidence: 99%